Rosuvastatin pharmacokinetics and pharmacogenetics in white and Asian subjects residing in the same environment - Lee, Edmund; Ryan, Stephen; Birmingham, Bruce; Zalikowski, Julie; March, Ruth; Ambrose, Helen; Moore, Rachael; Lee, Caroline; Chen, Yusong; Schneck, Dennis (Clinical pharmacology and therapeutics, 2005)
Systemic exposure to rosuvastatin had been observed to be approximately 2-fold higher in Japanese subjects living in Japan compared with white subjects in Western Europe or the United States. The organic anion transporting polypeptide 1B1 contributes to the hepatic uptake of rosuvastatin. Polymorphisms in the SLCO1B1 gene can lead to reduced transport function in vitro (T 521>C). This study was conducted to determine whether the pharmacokinetic differences between Japanese and white subjects extended to other Asian ethnic groups and to determine whether polymorphisms in the SLCO1B1 gene contribute to any pharmacokinetic differences observed. Rosuvastatin pharmacokinetics was studied in an open-label, parallel-group, single-oral dose (40 mg) study in 36 white, 36 Chinese, 35 Malay, and 35 Asian-Indian subjects living in Singapore, Singapore. Plasma concentrations of rosuvastatin and metabolites were determined by HPLC-mass spectrophotometry. Two SLCO1B1 polymorphisms (A 388>G and T 521>C) were genotyped. Ratios for rosuvastatin area under the plasma concentration-time curve from time 0 to the time of the last quantifiable concentration were 2.31, 1.91, and 1.63 and ratios for maximum plasma concentration were 2.36, 2.00, and 1.68 in Chinese, Malay, and Asian-Indian subjects, respectively, compared with white subjects. Similar increases in exposure to N-desmethyl rosuvastatin and rosuvastatin-lactone were observed. SLCO1B1 genotypes did not account for the observed pharmacokinetic differences between Asians and white subjects. Plasma exposure to rosuvastatin and its metabolites was significantly higher in Chinese, Malay, and Asian-Indian subjects compared with white subjects living in the same environment.